Customer Satisfaction, Customer Loyalty, and Market Orientation Through Service Quality: a case study of Islamic Banking in Indonesia - Rizkya Yunita Anggraini; Muhammad Iqbal Fasa; Suharto suharto (Sekolah Tinggi Ekonomi Islam (STEI) SEBI, 2022)
This study aims to examine: 1) the impact of marketplace orientation on client pleasure. 2) The impact of the carrier is great on patron pride. 3) the effect of marketplace orientation on customer loyalty. 4) the impact of provider satisfaction on patron loyalty. 5) the effect of consumer satisfaction on patron loyalty. 6) the effect of marketplace orientation on consumer loyalty via customer pleasure. 7) service great towards purchaser loyalty via client satisfaction. The sample of this examination is a hundred and seventy respondents; records series use on-line-survey. The evaluation approach used is Structural Equation Modeling with AMOS. The result is: 1) market orientation has a tremendous and sizable impact on purchaser satisfaction. 2) service best has a superb giant impact on client pleasure. 3) marketplace orientation has a trifling impact on customer loyalty. 4) carrier pleasantness has a tremendous-tremendous effect on consumer loyalty. 5) Customer delight has a superb-large effect on client loyalty. 6) marketplace orientation has an effective and extensive effect on consumer loyalty via purchaser satisfaction. 7) service satisfaction affects loyalty via patron pleasure. improve market orientation so that patron loyalty is stated through consumer satisfaction. further, enhance marketplace orientation through customer satisfaction to offer improved constancy to customers.